Pengaruh Pemanfaatan Aplikasi Quizizz Sebagai Media Pembelajaran Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PPKN Di SMP Yapia Pondok Aren: Jurnal Pendidikan - Fitri, Nurfitriani (Universitas Pamulang, 2024)
The aim of this research is to improve student learning outcomes in the learning process. The research approach used is quantitative. This research uses a quantitative approach, namely research that emphasizes analysis on numerical data or numbers processed using statistical methods. This research method is real experimental research or true experiment. The population in this study was class VIII of Yapia Pondok Aren Middle School for the 2022/2023 academic year with a total population of 375 students. The sample in this study used two classes for the experimental group treated with the quizizz application media, namely class VIII 5 consisting of 25 students. The control group that only used PowerPoint was class VIII 4 consisting of 25 students. The entire sample in this study was 50 students. The sampling technique in this research used the cluster random sampling technique and a research sample of 50 students was obtained. The data collection technique was by observing, pretest, posttest and questionnaire. The data analysis technique was using the prerequisite test, namely the normality test and homogeneity test. The data was said to be normal if the value Sig > 0.05 and it is said that the data is normally distributed. Research uses SPSS Version 27. There is an influence of the use of the Quizzizz application on learning outcomes. It can be seen from the results of the Independent Sample t-Test that the calculation results are Sig. (2-tailed) 0.003 < 0.05 which means that H0 is rejected and H